DETEKSI OTOMATIS DAERAH TERANG DI SISI JAUH MATAHARI UNTUK PREDIKSI KEMUNCULAN BINTIK - Muhamad Zamzam Nurzaman; Johan Muhamad; Rasdewita Kesumaningrum; Santi Sulistiani; Ayu Dyah Pangestu (Jurnal Sains Dirgantara, 2021)
Active regions that responsible to flare occurrences often appear at east limb as mature active regions. Therefore, we use EUVI instrument onboard STEREO-A spacecraft to observe far-side extreme ultra violet (EUV) for the automatic detection system. The procedure running on the system is by combining the latest STEREO/EUVI and the SDO/AIA data into a single composite heliographic coordinate system map. Active regions are detected based on their intensities on the heliographic map and their duration after they are detected. The program has successfully detected far-side bright-regions in an automatically  near real-time system. 85 % of active regions that have been detected for more than 4 days appear in the east limb as sunspots. On the other hand, bright-regions that have detected between 2-3 days develop to be plagues or decay before reaching the east limb. We find that the different between the mean intensities of the bright-regions that develop to sunspot and no-sunspot regions is about 200 DN//s, which is insignificant to determine the threshold.